(untitled) (Experimental biology, 2019)
Alzheimer’s disease is a chronic, incurable neurodegenerative disease and the most common form of age-related dementia. The on-set of this disease among the elderly population is influenced by various factors such as lifestyle, stress levels, genetic predisposition, chronic diseases, and environmental factors. Intestinal microbiome is one of the factors affecting human health and is increasingly attracting the attention of scientists over the past 15 years. Intestinal microbiomes are a community of microorganisms that colonize the gastrointestinal tract and have a huge impact on human physiology both in health and during diseases. In recent years, considerable amount of information has accumulated regarding the notion that the composition of the intestinal microflora changes with respect to various pathological conditions of the human body, including neurodegenerative diseases. This review article, therefore discusses the relationship between intestinal microbiome and the brain and the role microorganisms inhabiting the gastro-enteric tract play in the development of Alzheimer’s disease. Keywords: brain, neurodegeneration, Alzheimer’s disease, amyloid-ß, gut, gut microbiom.